CONSTRUCTING ACCESSIBLE AND ENGAGING VIDEO NARRATIVES: METADISCOURSE MARKERS IN PSYCH2GO YOUTUBE CHANNEL - Maria Febrianti; Steffie Mega Mahardhika (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
The increasing consumption of mental health content on digital platforms has intensified the need for effective communication strategies that balance clarity and audience engagement. This study examines how metadiscourse markers function in Psych2Go YouTube video narratives to construct accessible and engaging edutainment discourse. Drawing on Hyland’s (2005) metadiscourse framework and employing Qualitative Content Analysis (Mayring, 2000), this study analyses three selected video transcripts. The findings reveal that interactive markers function as structural devices that organize and simplify complex psychological information, while interactional markers serve as relational tools that foster audience involvement and parasocial connection. More importantly, the study demonstrates that the effectiveness of Psych2Go’s narratives lies in the dynamic interplay between these two marker types, enabling the transformation of monologic discourse into a dialogic and relatable experience. These findings contribute to a more nuanced understanding of how linguistic strategies shape digital communication.